2021
DOI: 10.3390/nu13113741
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of French Children and Adolescents to Advertising for Foods High in Fat, Sugar or Salt

Abstract: Food marketing of products high in fat, sugar and salt (HFSS), including television advertising, is one of the environmental factors considered as a contributor to the obesity epidemic. The main objective of this study was to quantify the exposure of French children and adolescents to television advertisements for HFSS products. TV food advertisements broadcast in 2018 were categorized according to the Nutri-Score of the advertised products. These advertisements, identified according to the days and times of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…According to a report by the European Commission, 64% of online advertisements and 75% of TV spots for food and beverages shown to children in Europe in 2017–2019 were for HFSS foods [ 14 ]. In France, 70.0% of products advertised on TV to 4- to 12-year-olds in 2018 should not be shown to children according to the criteria of the WHO Europe Nutrient Profile Model [ 15 ] and 53.3% were classified Nutri-Score groups D and E [ 11 , 16 ]. Moreover, advertisements targeting children mainly promote ultra-processed foods (UPFs) according to observations made around schools [ 17 , 18 , 19 ] and children’s TV shows (98.9% of spots for UPFs in Argentina [ 20 ]).…”
Section: Introductionmentioning
confidence: 99%
“…According to a report by the European Commission, 64% of online advertisements and 75% of TV spots for food and beverages shown to children in Europe in 2017–2019 were for HFSS foods [ 14 ]. In France, 70.0% of products advertised on TV to 4- to 12-year-olds in 2018 should not be shown to children according to the criteria of the WHO Europe Nutrient Profile Model [ 15 ] and 53.3% were classified Nutri-Score groups D and E [ 11 , 16 ]. Moreover, advertisements targeting children mainly promote ultra-processed foods (UPFs) according to observations made around schools [ 17 , 18 , 19 ] and children’s TV shows (98.9% of spots for UPFs in Argentina [ 20 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The tendency to include products categorised as D or E seems common in marketing strategies most often including children's products (Richonnet et al, 2021) and is consistent with other authors' content analyses of food and drink advertising in mass media. In a study developed by Escalon et al (2021) in France, it was observed that foods belonging to categories D or E tend to be advertised on television in the time slots during which children watch on television. A similar trend is observed in Spain, where the marketing of foods or beverages viewed by children on television include 34% and 13% of products classified as D and E, respectively (Montaña et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that the ways in which retailers and the market promote food will directly influence children’s preferences, nutrition knowledge, and dietary patterns and further affect their nutrition intake and health [ 42 , 43 ]. Consumers, particularly caregivers, parents, and children, may be drawn to unhealthy food and acquire dietary habits as a result of repeated information created by the advertising, branding, and marketing of unhealthy foods, such as products that are high in fat, sugar, and salt [ 42 , 44 , 45 , 46 ]. Small- and medium-sized firms (SMEs) are important linkages between the industry and consumers in developing countries, but they have limited incentives to serve nutritious food to low-income consumers in the absence of targeted food subsidies.…”
Section: Reshaping Food Systems To Improve Nutritionmentioning
confidence: 99%